2019
DOI: 10.3389/fpubh.2019.00141
|View full text |Cite|
|
Sign up to set email alerts
|

Facilitating Collective Psychosocial Resilience in the Public in Emergencies: Twelve Recommendations Based on the Social Identity Approach

Abstract: Accumulated evidence demonstrates the centrality of social psychology to the behavior of members of the public as immediate responders in emergencies. Such public behavior is a function of social psychological processes—in particular identities and norms . In addition, what the authorities and relevant professional groups assume about the social psychology of people in emergencies shapes policy and practice in preparedness, response, and recovery. These assumptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
217
0
11

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 192 publications
(242 citation statements)
references
References 124 publications
14
217
0
11
Order By: Relevance
“…Our measures of protective and avoidant behavior were much more comprehensive than our measure of other-supporting behavior. As the crisis proceeds, various behaviors that support the community through donating food, equipment, and money, making masks, supporting each other through buying food, and taking care of children become important, and it is known that such communal behavior emerges in crises and can be stifled by authorities reacting the wrong way ( Solnit, 2009 ; Drury et al, 2019 ). Future studies should place more emphasis on such measures.…”
Section: Discussionmentioning
confidence: 99%
“…Our measures of protective and avoidant behavior were much more comprehensive than our measure of other-supporting behavior. As the crisis proceeds, various behaviors that support the community through donating food, equipment, and money, making masks, supporting each other through buying food, and taking care of children become important, and it is known that such communal behavior emerges in crises and can be stifled by authorities reacting the wrong way ( Solnit, 2009 ; Drury et al, 2019 ). Future studies should place more emphasis on such measures.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of physical and mental health, if the public responds to COVID-19 properly, it can stimulate the internal drive of the human body to fight against the challenge of the epidemic. On the contrary, if the reaction is inappropriate or excessive, exceeding the bottom line that the body can tolerate, it will naturally disrupt the balance of physical and psychological functions of the person and impair physical and mental health and even cause serious physical and mental illness (Drury et al, 2019;Lee et al, 2018) . Our study found that age and gender are associated with anxiety.…”
Section: Self-rating Anxiety Scale (Sas) and Self-rating Depression Smentioning
confidence: 99%
“…During the period of epidemic pressure, people's psychology, physiology and behavior change accordingly (2,3). If an individual's response is inappropriate or excessive, it can impact physical and mental health (4,5), causing anxiety, fear, insomnia, or somatic symptoms. A previous study revealed that psychological factors could play a crucial role in public health strategies to control epidemics and pandemics (6).…”
Section: Introductionmentioning
confidence: 99%